THE CONCEPT OF TEACHING MATERIAL DEVELOPMENT IN MODERN LEARNING FROM THE PERSPECTIVE OF LEARNING THEORY - Yonatan, Amandus; Maria S, Haratua Tiur; Afandi, Afandi; Suratman, Dede; Pancaning W, Elvi Rusmiyanto (Jurnal Kajian Pembelajaran dan Keilmuan, 2025)
This article examines the development of teaching materials in modern learning by drawing on key learning theories. Rapid advances in information and communication technology have shifted learning needs, requiring materials that are adaptive to contemporary students’ characteristics. Using a literature review method, the study analyzes how Constructivism, Behaviorism, and Cognitivism serve as theoretical foundations for designing effective technology-enhanced teaching materials. The findings highlight that strategically integrating these theories not only strengthens student engagement but also improves learning outcomes. This article contributes a clearer framework for applying learning theories in the development of digital teaching materials and offers concrete examples of classroom implementations that enhance interaction and motivation. The study provides practical insights for educators and developers seeking to design relevant and theory-driven materials in an increasingly dynamic digital learning environment.